(untitled) (The Journal of Building and Land Development, 2023)
Land acquisition for national developments and expansion of existing infrastructure requires Â large amount of money to compensate affected peopleâ€™s rights on land. Its application in Tanzania with reference to projects implemented in Dar es Salaam city has been associated with notable mismatches between the requirements of the law and the practice which may partly be explained by the financing modality adopted. Key interviews with acquiring authority officials for selected projects; a review of acquisition laws/valuation reports and surveys of 28 Project Affected Persons were adopted for data collection. Findings revealed that financing modalities adopted in most compulsory land acquisition projects was through government budget by 75% and mixing government budget cum debt at 18%. Moreover, dependence on government budget creates mismatch between the provisions of the law and the practice thereby resulting into project delays and insufficient compensation to Project Affected Persons limiting the project desired outcomes. The study recommends proper planning of finances prior to execution of land acquisition process. A combination of both equity and loan while adhering to governance principles and stipulated legal requirements are vital and can bridge the funding gap into successful Compulsory land acquisition and projects implementation. Key words: Land Acquisition, Financing Modalities, Laws, Project Affected Persons